2022
DOI: 10.3390/md20060353
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Immunoregulatory Activities of TS40, a Derived Peptide of a TFPI-2 Homologue from Black Rockfish (Sebastes schlegelii)

Abstract: Tissue factor pathway inhibitor-2 (TFPI-2) is a Kunitz-type serine protease inhibitor. Previous reports have shown that TFPI-2 plays an important role in innate immunity, and the C-terminal region of TFPI-2 proved to be active against a broad-spectrum of microorganisms. In this study, the TFPI-2 homologue (SsTFPI-2) of black rockfish (Sebastods schegelii) was analyzed and characterized, and the biological functions of its C-terminal derived peptide TS40 (FVSRQSCMDVCAKGAKQHTSRGNVRRARRNRKNRITYLQA, corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The low toxicity of AMPs has been previously documented, pointing to this feature as a key factor for its use in several fields and among different species [51], and it also occurs in our study. Afterwards, we evaluated their immunomodulatory potential by exposing HK cells to a range of peptide concentrations from 5 to 200 µg/mL for 6 h, according to previous studies in other species [14,35,[52][53][54]. Unfortunately, respiratory burst and phagocytic activities were unaltered by the tested AMPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low toxicity of AMPs has been previously documented, pointing to this feature as a key factor for its use in several fields and among different species [51], and it also occurs in our study. Afterwards, we evaluated their immunomodulatory potential by exposing HK cells to a range of peptide concentrations from 5 to 200 µg/mL for 6 h, according to previous studies in other species [14,35,[52][53][54]. Unfortunately, respiratory burst and phagocytic activities were unaltered by the tested AMPs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, mudskipper (Boleophthamus pectinirostris) macrophages exposed to 1 µg/mL Nkl for 8 h had unaltered phagocytic ability but increased bactericidal ability [13]. Otherwise, the ability of Nkl to enhance the respiratory burst has been described both at shorter (1 h of incubation with 1 µg/mL of peptide) and longer (12 h with 10, 20, 50, and 80 µM) stimulation times in barbel steed (Hemibarbus labeo) and in black rockfish (Sebastes schlegelii), respectively [14,53,54]. The notable differences observed among species might suggest that even if Nkl peptides are highly conserved, the immunomodulation elicited by each peptide can be speciesdependent.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, insects represent a rich source for the discovery of new AMPs. Many studies have confirmed the biological functions of AMPs, such as their anticancer (Bao et al, 2021 ; Timmons and Hewage, 2022 ), antiviral (Liu R. et al, 2022 ; Nabeta et al, 2022 ; Nikyar et al, 2022 ), antibacterial (Maleki Dizaj et al, 2022 ; Wang et al, 2022b ) and immunoregulatory activities (Liu et al, 2018 ; Liu H. et al, 2022 ). There are also some reports on the anti- C. albicans activity of AMPs (Hu et al, 2022 ; Nabeta et al, 2022 ; Peng-Wei et al, 2022 ).…”
Section: Introductionmentioning
confidence: 95%
“…The peptide was purified to 96.66% via high performance liquid chromatography (HPLC), and it was identified using mass spectrometry (MS) analysis. The control peptide P86P15 (FKFLDNMAKVAPTEC), which is derived from a viral protein and is usually used as a negative control peptide, was synthesized in a similar manner [35,82,83]. Meanwhile, we synthesized the classical antimicrobial peptide Human hepcidin-25 (Hepc-25) in our studies.…”
Section: Peptides Synthesis and Structure Analysismentioning
confidence: 99%